2005
DOI: 10.1007/s11144-006-0016-4
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase oxidation of hydrogen sulfide to sulfur over CuO/MgO catalyst

Abstract: The effect of CuO loading on CuO/MgO catalysts was investigated for liquidphase oxidation of H 2 S to sulfur. CuO/MgO catalysts were prepared by impregnating MgO with aqueous copper nitrate solution. All of the catalysts were characterized by BET surface analyzer, X-ray diffraction (XRD), and temperature-programmed reduction (TPR). It was observed that the H 2 S removal capacity with respect to CuO loading increased up to 4 wt.%, and then decreased with further increase in CuO loading. CuO addition up to 4 wt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In a study on H 2 S control in oil containers, Nemati et al [9] reported that molybdate or formaldehyde, which is used mainly in the food industry, can be applied to inhibit microbial growth, but it is biodegrades easily in wastewater streams. Another way in which hydrogen sulfide formation can be eliminated for a long time is to slowly release oxygen in solid phases, such as MgO 2 and CaO 2 , which react with water to produce Mg(OH) 2 and Ca(OH) 2 , respectively [10,11]. Aguilar et al [12] draws our attention to using anodes for solid oxide fuel cells (SOFCs) operating in H 2 S-containing fuels, which suggests H 2 S is preferentially oxidized.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on H 2 S control in oil containers, Nemati et al [9] reported that molybdate or formaldehyde, which is used mainly in the food industry, can be applied to inhibit microbial growth, but it is biodegrades easily in wastewater streams. Another way in which hydrogen sulfide formation can be eliminated for a long time is to slowly release oxygen in solid phases, such as MgO 2 and CaO 2 , which react with water to produce Mg(OH) 2 and Ca(OH) 2 , respectively [10,11]. Aguilar et al [12] draws our attention to using anodes for solid oxide fuel cells (SOFCs) operating in H 2 S-containing fuels, which suggests H 2 S is preferentially oxidized.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, concrete and metal will be corroded by H 2 S [2]. Currently, absorption/adsorption and oxidation of H 2 S by ammonia [3], iron oxide [4], chelated iron [5], and zinc oxide [6] were applied broadly, but serious 'secondary pollution' would be caused by desulfurization equipments, complex operation processes and a large number of abandoned desulfurization solutions [7]. Many problems, such as low selectivity and efficiency, expensive desulfurizer and difficulty to recycle the sulfur affect the application of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed copper-magnesium oxide has been studied by many authors, since this material is highly active in several catalytic processes, including oxidation reactions [1,2] and the water-gas shift reaction [3]. Cu-MgO catalysts are commercially used for cyclohexanol conversion to cyclohexanone, and also proposed for other alcohol dehydrogenation processes [4,5] as well as to C=O bond hydrogenation [6,7], including a new route of methanol synthesis through ethyl formate [8,9].…”
Section: Introductionmentioning
confidence: 99%